Aladdin: little owl first readers - Humphreys, Clare; Guile, Gill (World International Great britain, 1990)
Aladdin tells the story of a poor young man who discovers a magical lamp containing a powerful genie. With the genie$1 (Bs help, Aladdin wins the heart of Princess Jasmine and battles the evil sorcerer Jafar to save the kingdom. The tale highlights themes of love, bravery, and the idea that true worth comes from within.s